Factors Influencing Teachers’ Performance in Junior High School - Hasbi Sjamsir, Usfandi Haryaka, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aims to determine whether work motivation affects teacher performance, discipline influences teacher performance, and teacher interpersonal communication affects teacher performance. Also, this research explores the prominent factors that influence teacher performance. This research was conducted at Samarinda Middle School with a sample of 60 randomly selected teachers from six Junior High Schools in Samarinda. The data were collected using a questionnaire, followed by interviews with five teacher representatives from each school. Furthermore, the data were analyzed by path analysis. The findings indicate that: (1) work motivation had a direct positive effect on teacher performance, (2) work discipline had a direct positive influence on teacher performance, (3) teacher interpersonal communication had a direct effect on teacher performance, and (4) the most dominant influential factor on teacher performance was teachers’ interpersonal communication.